What is Beyond Graduation for MENA Scholarship Alumni? Understanding the Global Journeys of Tomorrow’s Leaders Scholarship Alumni - Quradi, AlBaraa (AUC Knowledge Fountain, 2024)
The research conducted by the author delves deeply into the migration experiences of students from the Middle East and North Africa (MENA) region, with a specific focus on graduates of the Tomorrow's Leaders scholarship program. Through the use of a case study methodology, the study investigates the complex interconnections between migration, development, inequality, and the students' countries of origin. The investigation critically analyzes the aftermath of pursuing higher education on a scholarship basis, shedding light on how migration experiences are intertwined with broader issues of development and inequality in the MENA region. Furthermore, the research examines the factors that drive students to pursue further studies abroad and provides insights into the policies and procedures governing their movement and entry into countries of education. This contribution to the existing literature on the migration experiences of MENA scholarship recipients goes beyond by exploring the influence of social networks on migratory trajectories. The study emphasizes the need to understand the multifaceted factors that impact the mobility decisions of international students after graduation. The findings of the research reveal a complex interplay of influences on students' aspirations and migration plans, with the labor market and economic conditions playing crucial roles. The study indicates a growing trend where students intend to pursue higher education in third countries, influenced by social networks and family pressures. Furthermore, the research highlights the impact of historical events, such as the Arab Spring, which have contributed to increased emigration from the MENA region. In conclusion, this research underscores the dynamic interplay between external circumstances and individual choices in shaping the experiences of international students. The challenges associated with securing post-graduation prospects often lead to irregular employment situations, while host countries emerge as spaces for holistic growth and the formation of meaningful social connections. Additionally, the study sheds light on the phenomenon of students returning to their home countries, emphasizing the temporary respite sought and the desire to reconnect with familial roots. Ultimately, personal experiences and social networks are identified as central factors that shape the complex post-graduation plans of MENA scholarship recipients.